KOMPAS LESTARI: Sustainable Waste Management in Makartitama Village, Peninjauan District, Ogan Komering Regency, South Sumatra. - Richa Amalia; Erwin Hendra Putra; Sunarto Sunarto (Journal of Tropical Biodiversity, 2023)
Makartitama, located in PT. Pertamina Hulu Energi Ogan Komering's Ring 1 operational area, faces socio-economic challenges, with approximately 32% of its population living in poverty. These conditions have led to limited awareness of Clean and Healthy Living Behavior, resulting in higher disease prevalence and increased risk of stunting in children due to malnutrition. The Kompas Lestari program aims to empower the community and improve their well-being. Through systematic planning, execution, monitoring, and evaluation, the program involves all stakeholders, including local residents, other companies, NGOs, and community leaders. The heart of the initiative is Maggot Cultivation, utilizing the larvae of the Black Soldier Fly, an efficient organic waste decomposer. This practice significantly reduces waste accumulation, lowers pollution, and mitigates carbon emissions. Additionally, maggots offer a high-quality protein source and can be transformed into animal feed, benefiting local poultry and freshwater fish farming.The program has yielded positive results, creating new productive community groups and enhancing economic prospects. By fostering a value chain that includes waste collection, maggot cultivation, organic vegetable farming, and fish farming, the community experiences increased economic activity and improved nutrition. The success of Kompas Lestari has the potential to be replicated in other areas. However, the program requires continuous efforts and improvement to ensure sustainability and growth. Recommendations include strengthening cooperation with local companies for waste supply and exploring the use of oil palm waste as maggot feed. Moreover, improving the Maggot House infrastructure, conducting product analysis, and developing branding and marketing strategies for maggot-derived products are essential steps for expanding the program's impact and effectiveness